Bilgi Toplumunda Sosyal Bir Sorun: Stres ve Stresle Başa Çıkma Stratejileri - Recepoğlu, Serpil; Recepoğlu, Ergün (Kastamonu Üniversitesi, 2021)
Stress, which has become a social problem in recent years, can occur in all areas of life. In today's information societies, globalization and economic liberalization, trying to adapt to complex life conditions in an intensive information, communication and technology network cause him to feel pressured and wear out. In this context, stress is also expressed as "the disease of information society". This intensity affects the whole life of a person and reduces their self-esteem and efficiency. It is especially important to evaluate all aspects of stress from the individual's position, the state of environmental factors, from a sociological perspective. Natural disasters, epidemics, economic crises and wars have continued their effects on people for many years by affecting the masses and causing great losses. The ability of individuals to live happily and peacefully by protecting their health depends on their ability to manage stress well and to use effective coping strategies appropriate for them. In this study, strategies for coping with stress, which has become a social question in the information society, were examined all aspects of stress from the individual's position, the state of environmental factors, from a sociological perspective.

Son yıllarda sosyal bir sorun haline gelen stres hayatın her alanında ortaya çıkabilmektedir. Günümüz bilgi toplumlarında küreselleşme ve ekonomik liberalleşme, yoğun bir bilgi, iletişim ve teknoloji ağı içerisinde karmaşık yaşam koşullarına uyum sağlamaya çalışması, kendisini baskı altında hissetmesine ve yıpranmasına neden olmaktadır. Bu bağlamda stres, "bilgi toplumunun hastalığı" olarak da ifade edilmektedir. Bu yoğunluk, bir kişinin tüm yaşamını etkiler ve benlik saygısını ve verimliliğini azaltır. Stresin tüm yönlerini bireyin konumundan, çevresel faktörlerin durumundan, sosyolojik bir perspektiften değerlendirmek özellikle önemlidir. Doğal afetler, salgın hastalıklar, ekonomik krizler ve savaşlar, kitleleri etkileyerek ve büyük kayıplara neden olarak insanlar üzerindeki etkilerini uzun yıllar sürdürmüştür. Bireylerin sağlıklarını koruyarak mutlu ve barış içinde yaşayabilmeleri, stresi iyi yönetme ve kendileri için uygun etkili başa çıkma stratejileri kullanma becerilerine bağlıdır. Bu çalışmada, bilgi toplumunda sosyal bir sorun haline gelen stresle başa çıkma stratejileri, sosyolojik bir bakış açısıyla, kişisel, çevresel faktörlerin durumuna göre stresin tüm yönleri incelenmiştir.
Keywords: Eğitim Üzerine Çalışmalar; stres; stresle başa çıkma stratejileri; stres yönetimi; sosyal bir sorun; bilgi toplumu; Studies on Education